Change leadership in higher education : a practical guide to academic transformation - Buller, Jeffrey L. (Jossey-Bass, 2015)
"Initiate innovation and get things done with a guide to the process of academic changeChange Leadership in Higher Education is a call to action, urging administrators in higher education to get proactive about change. The author applies positive and creative leadership principles to the issue of leading change in higher education, providing a much-needed blueprint for changing the way change happens, and how the system reacts. Readers will examine four different models of change and look at change itself through ten different analytical lenses to highlight the areas where the current approach could be beneficially altered. The book accounts for the nuances in higher education culture and environment, and helps administrators see that change is natural and valuable, and can be addressed in creative and innovative ways.The traditional model of education has been disrupted by MOOCs, faculty unions, online instruction, helicopter parents, and much more, leaving academic leaders accustomed to managing change. Leading change, however, is unfamiliar territory. This book is a guide to being proactive about change in a way that ensures a healthy future for the institution, complete with models and tools that help lead the way. Readers will: Learn to lead change instead of simply "managing" it Examine different models of change, and redefine existing approaches Discover a blueprint for changing the process of change Analyze academic change through different lenses to gain a wider perspective Leading change involves some challenges, but this useful guide is a strong conceptual and pragmatic resource for forecasting those challenges, and going in prepared. Administrators and faculty no longer satisfied with the status quo can look to Change Leadership in Higher Education for real, actionable guidance on getting change accomplished"--